Pengembangan Media Flipbook Digital Pada Pembelajaran Menulis Puisi Siswa Kelas V SD Negeri 3 Mojorejo - Khusnatul Mawaddah Al-Habibah; Khasanah, Linaria Arofatul Ilmi Uswatun; Zativalen, Oriza (Jurnal Kiprah Pendidikan, 2025)
The learning of poetry writing is an important activity aimed at developing students' language skills and creativity. This study aims to develop digital flipbook media for poetry writing learning. The methodology used in this research is the Research and Development model with the ADDIE approach, which consists of analysis, design, development, implementation, and evaluation. The subjects of this study are 23 fifth-grade students at SD Negeri 3 Mojorejo. The instruments used for data collection include expert validation, student response questionnaires, and student activity questionnaires. The results indicate that the developed digital flipbook media is highly valid, with percentages of 97% from media experts, 95.25% from content experts, and 94.50% from design experts. The practicality of the media is also evidenced by student response questionnaire results, showing percentages of 87.5% in small-scale trials and 90.57% in large-scale trials, categorized as very practical. In conclusion, the digital flipbook media can be utilized as an innovative alternative in the poetry writing learning process, providing an engaging and enjoyable learning experience for students